The Construct Validity and Reliability of an Assessment Tool for Competency in Cochlear Implant Surgery. (10th July 2014) - Piromchai, Patorn; Kasemsiri, Pornthep; Wijewickrema, Sudanthi; Ioannou, Ioanna; Kennedy, Gregor; O'Leary, Stephen
Abstract : Introduction . We introduce a rating tool that objectively evaluates the skills of surgical trainees performing cochlear implant surgery. Methods . Seven residents and seven experts performed cochlear implant surgery sessions from mastoidectomy to cochleostomy on a standardized virtual reality temporal bone. A total of twenty-eight assessment videos were recorded and two consultant otolaryngologists evaluated the performance of each participant using these videos. Results . Interrater reliability was calculated using the intraclass correlation coefficient for both the global and checklist components of the assessment instrument. The overall agreement was high. The construct validity of this instrument was strongly supported by the significantly higher scores in the expert group for both components. Conclusion . Our results indicate that the proposed assessment tool for cochlear implant surgery is reliable, accurate, and easy to use. This instrument can thus be used to provide objective feedback on overall and task-specific competency in cochlear implantation.